Recurrent pleuresy due to a perforated and occluded peptic ulcer - Croci, Fabio; Gastambide, Carmelo; Rabellino, Joaquín; Gateño, Nisso; Belloso, Rogelio (Cirugía del Uruguay, 1983)
... A case of gastroduodenal peptic ulcer perforated and occluded is presented. The clinical presentation was a recurrent right pleuresy and in the e volution was interpreted as a carcinomatous peritoneal seeding. The correct diagnosis was done at laparotomy and confirmed posteriorly by fibergastroscopy. Drainage of subdiaphragmatic abcess solved the case. This es a rare clinical presentation.